On computation of limiting coderivatives of the normal-cone mapping to inequality systems and their applications. (2nd April 2016) - Gfrerer, Helmut; Outrata, Jiří V.
Abstract : The paper concerns the computation of the limiting coderivative of the normal-cone mapping related to inequality constraints under weak qualification conditions. The obtained results are applied to verify the Aubin property of solution maps to a class of parameterized generalized equations.